Knowledge Management in the Literature From 2021 to 2024 - Crespo, Julio E; Valdés, Jorge Hernández; Muñoz, Enrique Martínez; Ruíz, Gilberto Bermúdez; García Lirios, Cruz; Sepúlveda, Juan Guillermo Mancilla (International Journal Linguistics of Sumatra and Malay, 2024)
The COVID-19 pandemic has significantly impacted knowledge management in Higher Education Institutions (HEIs). Studies have found that material, financial, and human resources are the key factors in the knowledge network, and mistrust often exists between decision-makers and those who carry out the work. This study aimed to investigate the relationship between knowledge management and trust by conducting a cross-sectional, exploratory, and correlational study with a sample of 10 professional practitioners and social workers involved in COVID-19 care. The study findings show that innovation, competitiveness, and efficiency are the central, unifying, and structural axes of information translation and knowledge transfer. These results are not extensive to the university community, and they are innovative because they highlight the importance of trust as the guiding principle of knowledge management.